Advances in automation and robotics, Vol. 2 : Selected Papers from the 2011 International Conference on Automation and Robotics (ICAR 2011), Dubai, December 1-2, 2011 - Lee, Gary (Lecture Notes in Electrical Engineering, 2012)
The international conference on Automation and Robotics-ICAR2011 is held during December 12-13, 2011 in Dubai, UAE. The conference is intended to bring together the researchers and engineers/technologists working in different aspects of intelligent control systems and optimization, robotics and automation, signal processing, sensors, systems modeling and control, industrial engineering, production and management. This part of proceedings includes 82 papers contributed by many researchers in relevant topic areas covered at ICAR2011 from various countries such as France, Japan, USA, Korea and China etc.  The session topics of this proceedings are signal processing and industrial engineering, production and management, which includes papers about signal reconstruction, mechanical sensors, real-time systems control system identification, change detection problems, business process modeling, production planning, scheduling and control, computer-based manufacturing technologies, systems modeling and simulation, facilities planning and management, quality control and management, precision engineering, intelligent design and manufacturing. The papers in this proceedings focus on industry engineering to promote efficiency and affect for the world, which typically showed their advanced research work recently in their various field.